Sleep loss and change detection in driving scenes. (August 2018) - Filtness, Ashleigh J.; Beanland, Vanessa
Highlights: Experimental investigation of sleep restriction impact on change blindness in driving scenes. Accuracy of change detection was maintained when sleepy. Visual search strategy was maintained when sleepy. When sleepy, there is some evidence that drivers detect changes more slowly in urban images, but faster in rural images. Change blindness may be an influencing factor in urban but not rural sleep-related crashes. Abstract: Driver sleepiness is a significant road safety problem. Sleep-related crashes occur on both urban and rural roads, yet to date driver-sleepiness research has focused on understanding impairment in rural and motorway driving. The ability to detect changes is an attention and awareness skill vital for everyday safe driving. Previous research has demonstrated that person states, such as age or motivation, influence susceptibility to change blindness (i.e., failure or delay in detecting changes). The current work considers whether sleepiness increases the likelihood of change blindness within urban and rural driving contexts. Twenty fully-licenced drivers completed a change detection 'flicker' task twice in a counterbalanced design: once following a normal night of sleep (7–8 h) and once following sleep restriction (5 h). Change detection accuracy and response time were recorded while eye movements were continuously tracked. Accuracy was not significantly affected by sleep loss; however, following sleep loss there was some evidence of slowed change detection responses to urban images, but faster responses for rural images. Visual scanning across the images remained consistent between sleep conditions, resulting in no difference in the probability of fixating on the change target. Overall, the results suggest that sleep loss has minimal impact on change detection accuracy and visual scanning for changes in driving scenes. However, a subtle difference in response time to change detection between urban and rural images indicates that change blindness may have implications for sleep-related crashes in more visually complex urban environments. Further research is needed to confirm this finding.